Analytic and empirical study of the rate of convergence of some iterative methods - Vasile Berinde; Abdul Rahim Khan; Mădălina Păcurar (Journal of Numerical Analysis and Approximation Theory, 2015)
We study analytically and empirically the rate of convergence of two \(k\)-step fixed point iterative methods in the family of methods \[ x_{n+1}=T(x_{i_0+n-k+1},x_{i_1+n-k+1},\dots, x_{{i_{k-1}+n-k+1}}),\,n\geq k-1, \]